Cinema as dispositif: Between Cinema and Contemporary Art - Parente, André; de Carvalho, Victa (Cinémas)

(untitled) (Cinémas, 2008)
AbstractRecent upheavals in the media landscape raise two major issues. First, how is new media changing the cinematographic dispositif in its primordial dimensions: architectural (the conditions for image projection), technological (production, transmission and distribution) and discursive (cutting, editing, etc.)? How does experimentation in the field create new shifts or deviations with respect to the institutional mode of representation? Unlike the dominant cinema, some films reshape cinema’s dispositif by multiplying screens, exploring other durations and intensities, changing the architecture of the screening room or entering into other relations with spectators. In fact, cinema’s dispositif underwent variations such as these during three particular moments of film history, as we will discuss here: the cinema of attractions, expanded cinema and cinema of exhibition, whose differences will be analyzed through the notion of dispositif. While technological transformations are obvious in each of these moments, they also call attention to a series of experimentations with cinema’s dispositif which have been largely overlooked by film history. Not only do these deviations from a so-called institutional mode of representation produce new and heterogeneous subjectivities, they also have a decisive impact on recent film theory.